Labour economics - Smith, Stephen W. (Stephen Walter), 1955- (London : Routledge, 2003)
Now in its 2nd edition this comprehensive and accessible text provides a detailed study of labour market issues. This excellent new book is a must-see for all those involved in Labour Economics.
Book Cover; Title; Contents; Tables; Acknowledgements; Introduction; Labour supply; Labour demand and productivity; Wage determination and inequality; Personnel economics; Human capital; Labour market discrimination; Trade unions and labour markets; Labour market flexibility; Job search and vacancy analysis; Unemployment; Trade, globalisation and labour markets; Notes; Bibliography; Index.
Previous edition: 1994.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Labor economics; Économie du travail; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Labor economics; Electronic book